Edukasi Anti-Bullying bagi Siswa Sekolah Dasar sebagai Upaya Menciptakan Lingkungan Belajar yang Aman dan Inklusif - Depita Kardiati; Risna Dewi; Ferizaldi Ferizaldi; Syarifah Chairunnisak; Jamiati KN (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2026)
A safe and inclusive learning environment is an important factor in supporting the educational process. However, various forms of bullying behavior, such as teasing, giving negative nicknames, and social exclusion, are still found in schools and may hinder the creation of a comfortable and child-friendly learning environment. This community service activity aimed to improve students’ understanding of bullying and its impacts, as well as to instill the values of mutual respect as an effort to create a safe and inclusive learning environment. The activity was conducted at SD Negeri 2 Muara Batu, Aceh Utara Regency, through the XXXVIII Community Service and Empowerment Program (KKN-PPM) of Malikussaleh University in 2026. The methods used were educational and participatory approaches implemented through preparation, implementation, and evaluation stages. The activities were carried out through socialization sessions, discussions, question-and-answer sessions, simulations, and educational games. The results showed an improvement in students’ understanding of the forms, causes, and impacts of bullying, including verbal, physical, and social bullying. In addition, students demonstrated more positive attitudes, such as increased awareness of respecting differences, treating peers with respect, reducing teasing behavior, and developing empathy and concern for others. The activity also received positive responses from the school, as it was considered supportive of character education and the creation of a more conducive learning atmosphere. Therefore, anti-bullying education through educational and participatory approaches can serve as an effective strategy for creating a safe, comfortable, and inclusive learning environment for elementary school students.